Prevention of a parastomal hernia by biological mesh reinforcement - Fortelny, René H.; Hofmann, Anna; May, Christopher; Köckerling, Ferdinand (Frontiers in Surgery, 2015)
Introduction: In the field of hernia prevention the prophylactic mesh-reinforcement of stoma-sites is one of the most controversially discussed issues. The incidence of parastomal hernias in the literature reported to be up to 48.1% after end colostomy and up to 30.8 % after of loop colostomy respectively, but still remains uncertain due to diagnostic variety of clinical or radiological methods, heterogeneous patient groups and variable follow-up intervals respectively. Anyway, the published data regarding the use of synthetic or bio-prostethic meshes in the prevention of parastomal hernia at the primary operation are very scarce. Methods: A literature search of the Medline database in terms of biological prophylactic mesh implantation in stoma creation identified 6 systematic reviews, 2 randomized controlled trials (RCT), 2 case controlled studies and 1 technical report. Results: In a systematic review focusing on the prevention of parastomal hernia including only RCTs encompassing one RCT using bio-prosthetic mesh the incidence of herniation was 12.5 % compared to 53% in the control group (p<0.0001). In 1 RCT and 2 case control studies respectively, there was a significant smaller incidence of parastomal herniation as well as a similar complication rate compared to the control group respectively. Only in 1 RCT no significant difference regarding the incidence of parastomal hernia was reported with comparable complication rates. Conclusion: Thus so far 2 RCT and 2 case control studies are published with prophylactic bio prosthetic reinforcement in stoma sites. The majority revealed significant better results in terms of parastomal herniation and without any mesh related complications in comparison to the non mesh group. Further multicenter RCT are required to achieve a sufficient level of recommendation.